2010
DOI: 10.4414/smw.2010.13041
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective research: What are the ethical and legal requirements?

Abstract: Retrospective research is conducted on already available data and/or biologic material. Whether such research requires that patients specifically consent to the use of "their" data continues to stir controversy. From a legal and ethical point of view, it depends on several factors. The main criteria to be considered are whether the data or the sample is anonymous, whether the researcher is the one who collected it and whether the patient was told of the possible research use. In Switzerland, several laws delin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…possible research use (Junod & Elger, 2010). For example, if a manager of a health promotion program decides to conduct research with program data, only data collected after IRB approval may be included in the research.…”
Section: How Do I Know If My Project Is Research?mentioning
confidence: 99%
See 1 more Smart Citation
“…possible research use (Junod & Elger, 2010). For example, if a manager of a health promotion program decides to conduct research with program data, only data collected after IRB approval may be included in the research.…”
Section: How Do I Know If My Project Is Research?mentioning
confidence: 99%
“…Considerations related to IRB review, approval, and retrospective data depends on several factors—whether the data or sample is anonymous, whether the researcher collected the information or a third party, and whether those from whom the data was collected were told of the possible research use (Junod & Elger, 2010). For example, if a manager of a health promotion program decides to conduct research with program data, only data collected after IRB approval may be included in the research.…”
Section: Irb Reviewmentioning
confidence: 99%
“…A key issue to consider is the difference between anonymity and confidentiality . No study can be both.…”
Section: Research Involving Archived Materialsmentioning
confidence: 99%
“…It is possible to de‐identify samples, for example by pooling tissues or fluids from a number of patients. EVJ accepts research performed on anonymised samples can be considered for publication without informed consent from the animal owner, providing the owner is aware that the samples were being retained for research purposes ; however, material collected confidentially should have informed consent. We recognise that many studies are performed using materials collected some considerable time in the past and thus plan to set January 2019 as a deadline for zero tolerance of studies using confidential, archived materials that are lacking informed consent.…”
Section: Research Involving Archived Materialsmentioning
confidence: 99%
“…The design of a clinical trial implies adherence to challenging and multifaceted ethical and methodological standards that must integrate each other [ 4 ]; Ashton et al in their taxonomy indeed identified five major categories, with over 5900 possible standards [ 4 ]. Differences among research topics and study designs may add further variability in ethical requirements [ 5 8 ]. Research conducted with little methodological rigor does not lead to knowledge or benefit, and exposes participants to unnecessary burden or harm [ 9 ].…”
Section: Introductionmentioning
confidence: 99%